The Relationship between Psychosocial Stress and Coping Strategies for Breast Cancer Patients - Nihayati, Hanik Endang; Fadila, Firdha Lailil; Fauziningtyas, Rista (International Journal of Psychosocial Rehabilitation, 2020)
Breast cancer becomes a traumatic event for a woman’s life due to various influencing factors such as physical condition, self-image, sexuality, and social condition. One of the efforts that can be conducted to overcome these problems is by the coping strategies. The purpose of this study was to analyze the relationship between psychosocial stress and the coping strategies for breast cancer patients. The design of this study was cross-sectional research. The population in this study was 158 people, and the number of samples was 121 respondents selected using the consecutive sampling technique. The independent variable was psychosocial stress, while the dependent variable was the coping strategy. The instruments in this study were The Psychosocial Distress Questionnaire-Breast Cancer (PDQ-BC), and the Cancer Coping Questionnaire. Furthermore, data were analyzed using Spearman’s rho. Psychosocial stress experienced by most of the breast cancer patients was categorized as moderate stress, namely 75 (60.3%). The coping strategy applied mostly by breast cancer patients, was the maladaptive coping strategy, namely 71 (58.7%). There was a relationship between psychosocial stress and coping strategies for breast cancer patients (p = 0,000, r = -582). There is a moderate relationship between psychosocial stress and the maladaptive coping strategy. Therefore, nurses can convey to patients’ family members to continue and keep motivating the patients, and to help reduce anxiety, depression, physical condition, social condition, and sexual problems of the breast cancer patients.